2004
DOI: 10.1016/j.ehj.2003.12.007
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Syndrome is associated with advanced vascular damage in patients with coronary heart disease, stroke, peripheral arterial disease or abdominal aortic aneurysm

Abstract: In patients with manifest vascular disease the presence of the metabolic syndrome is associated with advanced vascular damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
114
1
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(126 citation statements)
references
References 43 publications
6
114
1
5
Order By: Relevance
“…22 In spite of the use of different and modified definitions, the metabolic syndrome is associated with more extensive vascular damage and increased risk for subsequent events in patients with prevalent cardiovascular disease. 12,23,24 In hypertensive patients without manifest vascular disease, the metabolic syndrome has been shown to be associated with increased intima-media thickness and left ventricular hypertrophy as well as with increased incidence of cardiovascular events. [25][26][27][28][29] It is not yet known whether the metabolic syndrome still is a predictor of new cardiovascular events in hypertensive patients with already clinically manifest cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…22 In spite of the use of different and modified definitions, the metabolic syndrome is associated with more extensive vascular damage and increased risk for subsequent events in patients with prevalent cardiovascular disease. 12,23,24 In hypertensive patients without manifest vascular disease, the metabolic syndrome has been shown to be associated with increased intima-media thickness and left ventricular hypertrophy as well as with increased incidence of cardiovascular events. [25][26][27][28][29] It is not yet known whether the metabolic syndrome still is a predictor of new cardiovascular events in hypertensive patients with already clinically manifest cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic syndrome (MetS) is interrelated atherosclerotic risk factors including insulin resistance, hypertension, a low level of high-density lipoprotein (HDL) cholesterol, a high triglyceride level, a high plasma glucose concentration, central obesity, and the increased number of components of the metabolic syndrome is associated with a higher mean carotid intima media thickness, lower ankle brachial pressure index in patients with coronary heart disease, peripheral arterial disease, or abdominal aortic aneurysm [3][4][5].…”
Section: Editorialmentioning
confidence: 99%
“…The metabolic syndrome (MetS) is interrelated atherosclerotic risk factors including insulin resistance, hypertension, a low level of high-density lipoprotein (HDL) cholesterol, a high triglyceride level, a high plasma glucose concentration, central obesity, and the increased number of components of the metabolic syndrome is associated with a higher mean carotid intima media thickness, lower ankle brachial pressure index in patients with coronary heart disease, peripheral arterial disease, or abdominal aortic aneurysm [3][4][5].Hajsadeghi et al reported a study with 100 patients with MetS (group I) and 100 control (group II) who experienced acute myocardial infarction. In this study the left ventricle (LV) was divided into six basal segments (anterior, anterolateral, inferolateral, inferior, inferoseptal, and anteroseptal), six middle segments (same subgroups), and four apically located segments (anterior, septal, inferior, and posterior).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes monitoring for protein glycation, an essential element for the long-term control of the complications of diabetes mellitus, is currently managed by a combination of daily self-monitoring of blood glucose (SMBG) measurements and physician-assessed hemoglobin A1c (A1C) levels every 3-6 months. 4,5,6,7,8 Figure I-Factors involved in pathogenesis of Diabetic Nephropathy…”
Section: Introductionmentioning
confidence: 99%